1996
DOI: 10.1053/jhep.1996.v23.pm0008666343
|View full text |Cite
|
Sign up to set email alerts
|

n-Butyrate induces plasminogen activator inhibitor type 1 messenger RNA in cultured Hep G2 cells

Abstract: n-Butyrate, a short-chain aliphatic carboxylic acid with pleiotropic actions, is present at high concentrations in the portal circulation and thus may play an important role in the regulation of specific gene expression in the mammalian liver. We report here that n-butyrate can increase substantially the level of plasminogen activator inhibitor type 1 (PAI-1) messenger RNA (mRNA) in Hep G2 cells, up to eightfold above control cultures. Maximal effects occurred at a concentration of 3 mmol/L n-butyrate and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…in the signal of the Charcot-Leyden crystal gene using HL-60 cells exposed to SB for 48 h. The exposure time (48 h) indicates that the increase is not a primary effect of SB. Smith et al [43], on the other hand, reported a decrease in the signal of the plasminogen activator inhibitor type 1 gene using Hep G2 cells treated with n-butyrate. As butyrate did not affect [41] (or even decreased [43]) the stability of the mRNAs in experiments using actinomycin D, neither transcriptional activation nor stabilization of the mRNA accounted for the increase in the steady-state level of the mRNA [43].…”
Section: Discussionmentioning
confidence: 99%
“…in the signal of the Charcot-Leyden crystal gene using HL-60 cells exposed to SB for 48 h. The exposure time (48 h) indicates that the increase is not a primary effect of SB. Smith et al [43], on the other hand, reported a decrease in the signal of the plasminogen activator inhibitor type 1 gene using Hep G2 cells treated with n-butyrate. As butyrate did not affect [41] (or even decreased [43]) the stability of the mRNAs in experiments using actinomycin D, neither transcriptional activation nor stabilization of the mRNA accounted for the increase in the steady-state level of the mRNA [43].…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate did not enhance the activity of the ETL promoter in mammalian cells Several studies have shown that histone deacetylase (HDAC) inhibitors, such as butyrate, can effectively enhance protein expression in mammalian cells [18,19] . To clarify whether the baculovirus early genedependent ETL promoter can also be enhanced by butyrate, we added 10 mmol/L butyrate to the COS-1 cell culture medium after transduction with vAcR-IR-G or vGS-EV71 ( Figure 5).…”
Section: Activity Of the Etl Promoter In Mammalian Cells Is Baculovirmentioning
confidence: 99%
“…Sodium butyrate (NaBu) is one of the most commonly used chemical additives in mammalian cell culture and is a known protein enhancer in CHO cells. NaBu improves productivity of recombinant proteins in CHO cells by hyperacetylation of histones, especially H4 by inactivation of histone deacetylase and changes in chromatin structure [16], NaBu causes over expression of mRNAs coding for a variety of proteins [17,18]. However, increased apoptosis was also observed by the addition of NaBu in these cultures [19].…”
Section: Introductionmentioning
confidence: 99%